A study of prevalence of thyroid disorders in type 2 diabetic patients in tertiary care hospital - Reddy, K. Sankar; Pragnanjali, E.; Dorsanamma, M.; Nagabushana, M. V. (International Journal of Advances in Medicine, 2018)
Background: Insulin and thyroid being intimately involved in cellular metabolism, excess or deficit of one of these hormones leads to abnormality of the other. Association between type 1diabetes and hypothyroidism may be autoimmune. Association of poorly controlled diabetes and thyroid results in a low T3 state and loss of TSH response to TRH. The objective of the present endeavor is to study the thyroid functions in diabetics and to know the spectrum of thyroid dysfunction in DM. Methods: It is a prospective cross-sectional study of 100 diabetic patients admitted in medical wards in a duration of 6 months from November 2017 to May 2018 of both sexes in between age group of 30-80years. All these patients underwent thyroid profile tests. Detailed history and examination done on these patients. Results: Out of total 100 patients included in the study, thyroid disorder was present in 29%. Hypothyroidism in 1 patient, sub clinical hypothyroidism in 15 patients, hyperthyroidism was present in 13 patients. Females (36%) had high incidence than males (22%). Elderly people had higher incidence of subclinical hypothyroidism (18.2%), clinical features of hyperthyroidism present in 8 patients, Poor hypoglycemic control seen in hyperthyroid individuals (55.5%). Duration of diabetes had no relation with incidence of thyroid disorders. Conclusions: Prevalence of thyroid disorders in diabetic patients was 29%. Elderly population had more incidence. Subclinical hypothyroidism more common than other conditions. It was more common in females than in males. There is no relation in between duration of diabetes and thyroid disorder. Severe complications were noted in patients with sub clinical hypothyroidism.